Laminated glass and vehicle

CN119894699APending Publication Date: 2025-04-25FUYAO GLASS IND GROUP CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280100200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-09-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing window glass has deficiencies in strength and safety, and is heavy, which affects the overall energy consumption and sound insulation effect of the vehicle.

Method used

A laminated glass design with an asymmetric structure is adopted, in which the thickness of the first glass substrate is greater than that of the second glass substrate, and the thickness of the first adhesive layer is less than that of the second adhesive layer. This laminated structure improves the overall mechanical strength and sound insulation effect, and Maximize load-bearing performance and cushioning effects by adjusting the thickness and stiffness of each layer.

Benefits of technology

The realization of high-strength, low-weight window glass improves the safety performance and sound insulation effect of the vehicle, while reducing the total weight of the vehicle and reducing energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894699A_ABST
    Figure CN119894699A_ABST
Patent Text Reader

Abstract

The invention provides laminated glass and a vehicle comprising the laminated glass, the laminated glass comprises a first glass substrate (1), a first bonding layer (2), a first functional layer (3), a second bonding layer (4) and a second glass substrate (5), and the first glass substrate, the first bonding layer, the first functional layer, the second bonding layer and the second glass substrate are sequentially stacked. The thickness of the first glass substrate is larger than that of the second glass substrate, and the thickness of the first bonding layer is smaller than that of the second bonding layer. The laminated glass is of an asymmetric structure, the thickness of the stress side face of the laminated glass is increased, the thickness of the non-stress side face of the laminated glass is reduced, the overall mechanical strength of the laminated glass is improved, the weight of the laminated glass is reduced, and the sound insulation effect of the laminated glass is further improved through the asymmetric structure.
Need to check novelty before this filing date? Find Prior Art

Description

Laminated glass and vehicle Technical Field

[0001] The present application relates to the technical field of vehicle glass, and in particular to a laminated glass and a vehicle. Background Art

[0002] Vehicle windows are an important component of a vehicle, allowing drivers to observe the outside environment and ensure driving safety. Window glass is required to have safety performance parameters such as high strength. At the same time, there is also a demand to reduce weight, so as to reduce the total weight of the vehicle by reducing the weight of the window, thereby reducing the vehicle's energy consumption.

[0003] Summary of the Invention

[0004] The technical problem to be solved by the present application is to provide a high-strength, low-weight vehicle window glass. To this end, the present application provides a laminated glass and a vehicle, wherein the laminated glass is designed to have an asymmetric structure. By increasing the thickness of the stress-bearing side of the laminated glass and reducing the thickness of the non-stress-bearing side of the laminated glass, the overall mechanical strength of the laminated glass is improved and the weight of the laminated glass is reduced. Moreover, the asymmetric structure described in the present application also improves the sound insulation effect of the laminated glass.

[0005] The technical solution adopted by the present application to solve the technical problem is: a laminated glass, comprising a first glass substrate, a first adhesive layer, a first functional layer, a second adhesive layer, and a second glass substrate, wherein the first glass substrate, the first adhesive layer, the first functional layer, the second adhesive layer, and the second glass substrate are stacked in sequence; the thickness of the first glass substrate is greater than that of the second glass substrate, and the thickness of the first adhesive layer is less than that of the second adhesive layer.

[0006] In a possible implementation manner, a ratio of the thickness of the first glass substrate to the thickness of the second glass substrate is 1.17:1 to 2.91:1.

[0007] In a possible implementation, a ratio of the thickness of the first glass substrate to the thickness of the second glass substrate is 1.17:1 to 1.5:1.

[0008] In a possible implementation, a ratio of the thickness of the first adhesive layer to the thickness of the second adhesive layer is 1:8 to 1:1.1.

[0009] In a possible implementation, the mechanical strength of the first glass substrate is greater than the mechanical strength of the second glass substrate.

[0010] In a possible implementation, the hardness of the second bonding layer is less than that of the first bonding layer.

[0011] In a possible implementation, the first functional layer is at least one of an infrared reflective layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film.

[0012] In a possible implementation, the first functional layer is a third glass substrate, the thickness of the first glass substrate is greater than the thickness of the third glass substrate, and the thickness of the third glass substrate is greater than the thickness of the second glass substrate.

[0013] In a possible implementation manner, a ratio of the thickness of the first glass substrate, the thickness of the third glass substrate, and the thickness of the second glass substrate is (2.91 to 2):(2 to 1.17):1.

[0014] In a possible implementation manner, a ratio of the thickness of the first glass substrate, the thickness of the third glass substrate, and the thickness of the second glass substrate is (1.5 to 1.3):(1.3 to 1.17):1.

[0015] In a possible implementation, the mechanical strength of the first glass substrate is greater than that of the third glass substrate, and the mechanical strength of the third glass substrate is greater than that of the second glass substrate.

[0016] In a possible embodiment, the laminated glass further includes a second functional layer and a connecting layer, wherein the second functional layer is arranged between the first functional layer and the second adhesive layer, and the connecting layer is arranged between the first functional layer and the second functional layer for connecting the first functional layer and the second functional layer.

[0017] In a possible implementation, the thickness of the first functional layer is greater than the thickness of the second functional layer.

[0018] In a possible implementation, a ratio of the thickness of the first functional layer to the thickness of the second functional layer is 2:1 to 3:1.

[0019] In a possible implementation manner, the hardness of the first functional layer is greater than the hardness of the second functional layer.

[0020] In a possible implementation, the thickness of the connecting layer is 0.1 mm to 0.4 mm.

[0021] In a possible implementation, the thickness of the connecting layer is 0.1 mm to 0.2 mm.

[0022] In a possible implementation, the second functional layer is at least one of an infrared reflective layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film.

[0023] In a possible implementation, the laminated glass further includes a touch film layer, which is disposed between the second glass substrate and the second adhesive layer, and is used to detect touch signals.

[0024] The present application also provides a vehicle, comprising:

[0025] the vehicle body; and

[0026] In the laminated glass described in the present application, the first glass substrate faces the outside of the vehicle body, and the second glass substrate faces the inside of the vehicle body.

[0027] The laminated glass described in the present application can be used in enclosed spaces such as vehicles, buildings, and instruments, so that the external environment of the enclosed space or the internal situation of the enclosed space can be observed through the laminated glass; the first glass substrate of the laminated glass is a component that directly bears external pressure. When external pressure acts on the laminated glass, the impact caused by the external pressure first acts on the first glass substrate, and is then received and absorbed by the first glass substrate and then transmitted to the second glass substrate. In this process, the first glass substrate bears the most impact, and then the impact caused by the external pressure will gradually weaken, resulting in the second glass substrate bearing less impact, resulting in the bearing capacity of the second glass substrate not being fully utilized and redundancy occurring. In the solution described in the present application, the thickness of the first glass substrate that is most affected by the external pressure is increased, and the thickness of the second glass substrate that is least affected by the external pressure is reduced. , which can maximize the bearing performance of the glass substrate, thereby improving the overall mechanical strength of the laminated glass described in the present application; after the laminated glass is subjected to external impact, the laminated glass will passively deform under the action of the external pressure. The first adhesive layer is provided on the first glass substrate. When the external pressure acts on the laminated glass, the external pressure directly acts on the first glass substrate. At this time, the first adhesive layer is designed to be relatively thin and have a relatively high hardness, which is conducive to ensuring the stability of the connection between the first glass substrate and other components of the laminated glass; subsequently, when the impact caused by the external pressure reaches the second adhesive layer, the impact caused by the external pressure has been gradually weakened. At this time, the second adhesive layer is designed to be relatively thick and have a relatively low hardness, so as to absorb the deformation tendency of the laminated glass under the action of the external pressure, thereby achieving a buffering effect, thereby improving the overall stability of the laminated glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] FIG1 is a schematic diagram of the structure of laminated glass with a single functional film layer provided in an embodiment of the present application;

[0029] FIG2 is a schematic diagram of the structure of laminated glass with multiple functional film layers provided in an embodiment of the present application;

[0030] FIG3 is a schematic diagram of the laminated glass structure of the multi-layer glass substrate provided in an embodiment of the present application;

[0031] FIG4 is a schematic diagram of a vehicle provided in an embodiment of the present application.

[0032] Reference numerals:

[0033] 100-laminated glass; 200-vehicle; 1-first glass substrate; 2-first adhesive layer; 3-first functional layer; 4-second adhesive layer; 5-second glass substrate; 6-third glass substrate; 7-connecting layer; 8-second functional layer; 9-vehicle body. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of this application more clear, this application is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described here are only used to explain this application and are not used to limit this application.

[0035] In the description of the present application, it should be noted that the reference to "embodiment" or "implementation method" in the present application means that the specific features, structures or characteristics described in conjunction with the embodiment or implementation method may be included in at least one embodiment of the present application. The appearance of the phrase in various positions in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. The orientation or positional relationship indicated by the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or positional relationship shown in the accompanying drawings, and is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0036] In addition, the technical features involved in the different embodiments of the present application described above can be combined with each other as long as they do not conflict with each other.

[0037] Referring to FIG. 1 , a laminated glass 100 includes a first glass substrate 1, a first adhesive layer 2, a first functional layer 3, a second adhesive layer 4, and a second glass substrate 5. The first glass substrate 1, the first adhesive layer 2, the first functional layer 3, the second adhesive layer 4, and the second glass substrate 5 are stacked in sequence. The first glass substrate 1 is thicker than the second glass substrate 5, and the first adhesive layer 2 is thinner than the second adhesive layer 4.

[0038] Optionally, when the laminated glass 100 device described in the present application is used as a vehicle window glass in a vehicle, the surface of the first glass substrate 1 facing away from the second glass substrate 5 faces the exterior of the vehicle, and the surface of the second glass substrate 5 facing away from the first glass substrate 1 faces the interior of the vehicle. In other words, the surface of the first glass substrate 1 facing away from the second glass substrate 5 is an impact-receiving surface, an outer surface, or an appearance surface; the first glass substrate 1, the first adhesive layer 2, the first functional layer 3, the second adhesive layer 4, and the second glass substrate 5 are stacked in sequence. In other words, the first glass substrate 1 and the first functional layer 3 are bonded to each other via the first adhesive layer 2, and the first functional layer 3 and the second glass substrate 5 are bonded to each other via the second adhesive layer 4.

[0039] Optionally, when external pressure acts on the laminated glass 100, the impact caused by the external pressure first acts on the first glass substrate 1, and after being received and absorbed by the first glass substrate 1, is transmitted to the second glass substrate 5. The first glass substrate 1 bears more impact, and the second glass substrate 5 bears less impact. Therefore, in the present application, by making the thickness of the first glass substrate 1 greater than the thickness of the second glass substrate 5, the bearing capacity of the glass substrates is maximized, so that the overall mechanical strength of the laminated glass 100 of the present application is improved; after the laminated glass 100 is subjected to the impact caused by the external pressure, the laminated glass 100 will be deformed under the action of the external pressure. The first adhesive layer 2 is provided on the first glass substrate 1. When external pressure acts on the laminated glass 100, the external pressure acts directly on the first glass substrate 1. In this case, the first adhesive layer 2 is designed to be relatively thin, which helps to ensure the stability of the connection between the first glass substrate 1 and other components of the laminated glass 100. Subsequently, when the impact of the external pressure reaches the second adhesive layer 4, the impact of the external pressure has been gradually weakened. In this case, the second adhesive layer 4 is designed to be relatively thick and have a relatively low hardness, so as to absorb the deformation tendency of the laminated glass 100 under the action of external pressure, achieve a buffering effect, and thus improve the overall stability of the laminated glass 100.

[0040] In one possible embodiment, the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 is 1.17:1 to 2.91:1; specifically, the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 can be, but is not limited to, 1.17:1, 1.2:1, 1.4:1, 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1, 2.6:1, 2.8:1, or 2.91:1. In one possible embodiment, the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 is 1.17:1 to 1.5:1; specifically, the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 can be, but is not limited to, 1.17:1, 1.2:1, 1.23:1, 1.25:1, 1.27:1, 1.3:1, 1.33:1, 1.35:1, 1.37:1, or 1.4:1.

[0041] When external pressure acts on the laminated glass 100, the impact caused by the external pressure acts on the first glass substrate 1, is absorbed by the first glass substrate 1, and then transmitted to the second glass substrate 5. Since the first glass substrate 1 and the second glass substrate 5 bear different external impacts, the first glass substrate 1 bears more impact, and the second glass substrate 5 bears less impact. Therefore, in the present application, by controlling the thickness ratio of the first glass substrate 1 to the second glass substrate 5, the load-bearing performance of the first glass substrate 1 and the second glass substrate 5 is fully utilized to avoid redundancy. When the thickness ratio of the first glass substrate 1 to the second glass substrate 5 is 1.17:1 to 2.91:1, the load-bearing performance of the first glass substrate 1 and the second glass substrate 5 is fully utilized. ; Further, when the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 is 1.17:1 to 1.5:1; the bearing properties of the first glass substrate 1 and the second glass substrate 5 are more fully utilized, which is conducive to reducing the thickness of the laminated glass 100 and enhancing the mechanical strength of the laminated glass 100; when the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 is less than 1.17:1, the bearing properties of the second glass substrate 5 cannot be fully utilized, resulting in redundancy. The excessively thick second glass substrate 5 causes the overall thickness of the laminated glass 100 to increase while the mechanical strength remains unchanged; when the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 is greater than 2.91:1, the thickness of the first glass substrate 1 is too large, which is not conducive to thinning the laminated glass 100.

[0042] Optionally, the thickness of the first glass substrate 1 is 2.1 mm to 4.0 mm. Specifically, the thickness of the first glass substrate 1 may be, but is not limited to, 2.1 mm, 2.3 mm, 2.5 mm, 2.8 mm, 3.0 mm, 3.2 mm, 3.5 mm, or 4.0 mm.

[0043] Optionally, the thickness of the second glass substrate 5 is 1.1 mm to 2.1 mm. Specifically, the thickness of the second glass substrate 5 may be, but is not limited to, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.8 mm, 2.0 mm, or 2.1 mm.

[0044] Specifically, when the thickness of the first glass substrate 1 is 2.1 mm to 4.0 mm and the thickness of the second glass substrate 5 is 1.1 mm to 2.1 mm, the ratio of the thickness of the first glass substrate 1 to the thickness of the second glass substrate 5 still satisfies 1.17:1 to 2.91:1, so as to fully utilize the bearing performance of the first glass substrate 1 and the second glass substrate 5 and avoid redundancy; since the first glass substrate 1 is directly impacted by external forces, the mechanical strength of the first glass substrate 1 directly affects the mechanical strength of the laminated glass 100. When the thickness of the first glass substrate 1 is too thick, exceeding 4.0 mm, the bearing performance of the first glass substrate 1 itself will lead to redundancy in actual application scenarios, and the overly thick first glass substrate 1 will cause The laminated glass 100 has excessive and unnecessary weight. When the thickness of the first glass substrate 1 is too thin, less than 2.1 mm, the load-bearing capacity of the first glass substrate 1 itself is insufficient and cannot provide protection for the laminated glass 100. When the thickness of the second glass substrate 5 is too thick, exceeding 2.1 mm, the load-bearing capacity of the second glass substrate 5 cannot be fully utilized, resulting in redundancy. The excessively thick second glass substrate 5 increases the overall thickness of the laminated glass 100 while maintaining the mechanical strength. When the thickness of the second glass substrate 5 is too thin, less than 1.1 mm, the load-bearing capacity of the second glass substrate 5 is insufficient to withstand the impact of the external pressure transmitted from the first glass substrate 1, resulting in a weakening of the mechanical strength of the laminated glass 100 itself.

[0045] In one possible embodiment, the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4 is 1:8 to 1:1.1. Specifically, the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4 can be, but is not limited to, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, or 1:1.1. Furthermore, the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4 is 1:3 to 1:1.1.

[0046] When external pressure acts on the laminated glass 100, the laminated glass 100 will passively deform under the influence of the external pressure. Since the first glass substrate 1 will bear the greatest external pressure impact, the first adhesive layer 2 provided on the first glass substrate 1 is designed to be relatively thin to ensure the stability of the connection between the first glass substrate 1 and other components of the laminated glass 100. Subsequently, when the impact of the external pressure reaches the second adhesive layer 4, the impact of the external pressure has been gradually weakened. At this time, the second adhesive layer 4 is designed to be relatively thick to absorb the deformation tendency of the laminated glass 100 under the influence of the external pressure, thereby achieving a buffering effect. Therefore, in the present application, by controlling the thickness ratio of the first glass substrate 1 to the second glass substrate 5 to be between 1:8 and 1:1.1, the first adhesive layer 2 exhibits good stability and the second adhesive layer 4 exhibits good buffering properties, thereby improving the overall stability of the laminated glass 100.

[0047] Optionally, when the thickness of the first adhesive layer 2 is 0.1 mm to 0.38 mm; specifically, when the thickness of the first adhesive layer 2 can be but not limited to 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.38 mm.

[0048] Optionally, when the thickness of the second adhesive layer 4 is 0.38mm to 0.76mm; specifically, when the thickness of the second adhesive layer 4 can be but not limited to 0.38mm, 0.42mm, 0.46mm, 0.50mm, 0.54mm, 0.58mm, 0.62mm, 0.66mm, 0.70mm, 0.72mm, 0.76mm.

[0049] Optionally, when the sum of the thickness of the first adhesive layer 2 and the thickness of the second adhesive layer 4 is 1.14 mm, the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4 is 1:2; when the sum of the thickness of the first adhesive layer 2 and the thickness of the second adhesive layer 4 is 10.64 mm, the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4 is 1:6; in other words, the greater the sum of the thickness of the first adhesive layer 2 and the thickness of the second adhesive layer 4, the smaller the ratio of the thickness of the first adhesive layer 2 to the thickness of the second adhesive layer 4.

[0050] In one possible embodiment, the mechanical strength of the first glass substrate 1 is greater than that of the second glass substrate 5. When external pressure acts on the laminated glass 100, the impact generated by the external pressure acts on the first glass substrate 1, is absorbed by the first glass substrate 1, and then transmitted to the second glass substrate 5. Because the first glass substrate 1 and the second glass substrate 5 bear different external impacts, the first glass substrate 1 withstands more impact and the second glass substrate 5 withstands less impact. Therefore, in this application, the first glass substrate 1 can be made of a material with higher mechanical strength. In other words, when the first glass substrate 1 and the second glass substrate 5 are made of materials with the same mechanical strength, the first glass substrate 1 can be made of a material with a greater thickness to increase its strength, thereby allowing it to withstand greater impact from external pressure, thereby improving the mechanical strength of the laminated glass 100. Alternatively, the first glass substrate 1 can be made of a material with a higher mechanical strength than the second glass substrate 5, so that the first glass substrate 1 has a higher mechanical strength, allowing it to withstand greater impact from external pressure, thereby improving the mechanical strength of the laminated glass 100.

[0051] Optionally, the first glass substrate 1 is chemically tempered glass, and the second glass substrate 5 is tempered glass.

[0052] Specifically, the mechanical strength of the first glass substrate 1 is 500 MPa to 1100 MPa, and the mechanical strength of the second glass substrate 5 is 96 MPa to 120 MPa.

[0053] In one possible embodiment, the hardness of the second adhesive layer 4 is less than that of the first adhesive layer 2. When external pressure acts on the laminated glass 100, the laminated glass 100 will passively deform under the action of the external pressure. Since the first glass substrate 1 will bear the greatest impact of the external pressure, the first adhesive layer 2 disposed on the first glass substrate 1 is designed to be relatively thin, thereby ensuring that the first adhesive layer 2 is relatively large, thereby ensuring the stability of the connection between the first glass substrate 1 and other components of the laminated glass 100. Subsequently, when the impact of the external pressure reaches the second adhesive layer 4, the impact of the external pressure has been gradually weakened. At this time, the second adhesive layer 4 is designed to be relatively thick, thereby ensuring that the hardness of the second adhesive layer 4 is relatively low, thereby absorbing the deformation tendency of the laminated glass 100 under the action of the external pressure and achieving a buffering effect. In other words, by making the hardness of the first adhesive layer 2 greater than that of the second adhesive layer 4, the first adhesive layer 2 exhibits good stability, and the second adhesive layer 4 exhibits good buffering properties, thereby improving the overall stability of the laminated glass 100.

[0054] Optionally, the hardness of the second adhesive layer 4 is 40HA to 50HA; the hardness of the first adhesive layer 2 is 50HA to 60HA.

[0055] In a possible implementation, the first functional layer 3 is at least one of an infrared reflection layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film layer.

[0056] Optionally, the polymer dispersed liquid crystal film layer may be at least one of an SPD dimming film, an EC dimming film, and an LC dimming film.

[0057] The infrared reflection layer has a thickness ranging from 6 nm to 90 nm, and is used to reflect infrared rays in sunlight when the laminated glass 100 is used as a vehicle window glass to prevent the infrared rays from causing excessive temperature rise inside the vehicle; the ultraviolet absorption layer has a thickness ranging from 20 nm to 84 nm, and is used to absorb ultraviolet rays in sunlight when the laminated glass 100 is used as a vehicle window glass to prevent ultraviolet rays from damaging the skin of people inside the vehicle; the touch film layer has a thickness ranging from 37 nm to 132 nm, and is used to detect touch signals applied to the laminated glass 100; when the laminated glass 100 is used as a vehicle window glass, the touch film layer is used to detect touch signals and control components of the vehicle, such as window lights, sensor lights, ambient lights, sensors, processors, etc., based on the signals; the polymer dispersed liquid crystal film layer has a thickness ranging from 25 nm to 98 nm, and is used to adjust the transparent state or non-transparent state of the laminated glass 100 by changing to a transparent state or a non-transparent state.

[0058] Optionally, the laminated glass 100 obtained by sequentially stacking the first glass substrate 1, the first adhesive layer 2, the first functional layer 3, the second adhesive layer 4, and the second glass substrate 5 presents an asymmetric structure with the first functional layer 3 as the center. When sound waves propagate in the laminated glass 100 described in the present application, this asymmetric structure can increase the loss of the sound wave propagation process, thereby improving the sound insulation effect of the laminated glass 100 described in the present application when used in a vehicle.

[0059] 2 , in a possible implementation, the first functional layer 3 is a third glass substrate 6 , the thickness of the first glass substrate 1 is greater than that of the third glass substrate 6 , and the thickness of the third glass substrate 6 is greater than that of the second glass substrate 5 .

[0060] When external pressure acts on the laminated glass 100, the impact caused by the external pressure first acts on the first glass substrate 1. After being received and absorbed by the first glass substrate 1, the impact is then transmitted to the third glass substrate 6. After being received and absorbed by the third glass substrate 6, the impact is then transmitted to the second glass substrate 5. The first glass substrate 1 bears the greatest impact, the third glass substrate 6 bears the second greatest impact, and the second glass substrate 5 bears the least impact. Therefore, in the present application, the thicknesses of the first glass substrate 1, the third glass substrate 6, and the second glass substrate 5 are sequentially reduced to maximize the bearing capacity of the glass substrates, thereby improving the overall mechanical strength of the laminated glass 100 described in the present application.

[0061] In one possible embodiment, the thickness ratio of the first glass substrate 1, the thickness of the third glass substrate 6, and the thickness of the second glass substrate 5 is (2.91 to 2): (2 to 1.17): 1. Specifically, the thickness ratio of the first glass substrate 1, the thickness of the third glass substrate 6, and the thickness of the second glass substrate 5 can be, but is not limited to, 2.91:2:1, 2.8:2:1, 2.7:2:1, 2.6:2:1, 2.5:2:1, 2.4:1.8:1, 2.2:1.5:1, 2.2:1.2:1, 2:1.1.17:1; And the thickness ratio of the second glass substrate 5 is (1.5 to 1.3): (1.3 to 1.17): 1; specifically, the thickness ratio of the first glass substrate 1, the thickness of the third glass substrate 6 and the thickness of the second glass substrate 5 can be, but is not limited to, 1.5:1.3:1, 1.5:1.2:1, 1.5:1.17:1, 1.45:1.17:1, 1.4:1.17:1, 1.35:1.17:1, and 1.3:1.17:1. When the ratio of the thickness of the first glass substrate 1, the thickness of the third glass substrate 6, and the thickness of the second glass substrate 5 is (2.91 to 2): (2 to 1.17): 1, the load-bearing properties of the first glass substrate 1, the third glass substrate 6, and the second glass substrate 5 are more fully utilized, which is beneficial to reducing the thickness of the laminated glass 100 and enhancing the mechanical strength of the laminated glass 100. Furthermore, when the ratio of the thickness of the first glass substrate 1, the thickness of the third glass substrate 6, and the thickness of the second glass substrate 5 is (1.5 to 1.3): (1.3 to 1.17): 1, the load-bearing properties of the first glass substrate 1, the third glass substrate 6, and the second glass substrate 5 are more fully utilized, which is beneficial to reducing the thickness of the laminated glass 100 and enhancing the mechanical strength of the laminated glass 100.

[0062] Optionally, the thickness of the third glass substrate 6 is 1.4 mm to 3.2 mm. Specifically, the thickness of the third glass substrate 6 can be, but is not limited to, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, 2.1 mm, 2.2 mm, 2.2 mm, 2.3 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.7 mm, 2.8 mm, 2.9 mm, 3.0 mm, 3.1 mm, or 3.2 mm. The thickness of the third glass substrate 6 is between the thickness of the first glass substrate 1 and the thickness of the second glass substrate 5. By sequentially decreasing the thicknesses of the first glass substrate 1, the third glass substrate 6, and the second glass substrate 5, the bearing capacity of the glass substrates is maximized, thereby improving the overall mechanical strength of the laminated glass 100 of the present application.

[0063] In a possible implementation, the mechanical strength of the first glass substrate 1 is greater than the mechanical strength of the third glass substrate 6 , and the mechanical strength of the third glass substrate 6 is greater than the mechanical strength of the second glass substrate 5 .

[0064] When external pressure acts on the laminated glass 100, the impact caused by the external pressure acts on the first glass substrate 1, and after being received and absorbed by the first glass substrate 1, it is transmitted to the third glass substrate 6, and after being received and absorbed by the third glass substrate 6, it is transmitted to the second glass substrate 5. Since the first glass substrate 1, the third glass substrate 6 and the second glass substrate 5 receive different external impacts, the first glass substrate 1 bears the greatest impact, the third glass substrate 6 bears the second greatest impact, and the second glass substrate 5 bears the least impact. Therefore, in the present application, the first glass substrate 1 and / or the third glass substrate 5 can be made of a material with higher mechanical strength. In other words, when the first glass substrate 1, the third glass substrate 6, and the second glass substrate 5 are made of materials with the same mechanical strength, the first glass substrate 1 and the third glass substrate 6 can be increased in thickness to increase their own strength, so that they can withstand the impact of greater external pressure, thereby improving the mechanical strength of the laminated glass 100; or, the first glass substrate 1 and the third glass substrate 6 can be made of a material with higher mechanical strength than the second glass substrate 5, so that the first glass substrate 1 has higher mechanical strength, so that it can withstand the impact of greater external pressure, thereby achieving the purpose of improving the mechanical strength of the laminated glass 100.

[0065] Optionally, the laminated glass 100 further includes multiple glass substrates and multiple adhesive layers, wherein the multiple glass substrates are stacked between the first glass substrate 1 and the second glass substrate 5, and the multiple glass substrates are connected to the first glass substrate 1 and the second glass substrate 5 by the adhesive layers. In a direction from the first glass substrate 1 to the second glass substrate 5, the thickness of the multiple glass substrates passed through gradually decreases, while the thickness of the multiple adhesive layers passed through gradually increases; or, the mechanical strength of the multiple glass substrates passed through gradually decreases, while the hardness of the multiple adhesive layers passed through gradually decreases.

[0066] Optionally, the laminated glass 100 obtained by sequentially stacking the first glass substrate 1 , the first adhesive layer 2 , the third glass substrate 6 , the second adhesive layer 4 and the second glass substrate 5 has an asymmetric structure with the third glass substrate 6 as the center.

[0067] Referring to Figure 3, in one possible embodiment, the laminated glass 100 further includes a second functional layer 8 and a connecting layer 7. The second functional layer 8 is disposed between the first functional layer 3 and the second adhesive layer 4. The connecting layer 7 is disposed between the first functional layer 3 and the second functional layer 8 for connecting the first functional layer 3 and the second functional layer 8.

[0068] Optionally, the adhesive layer is used to connect the first functional layer 3 and the second functional layer 8, so that the first functional layer 3 and the second functional layer 8 constitute a functional layer group to provide the laminated glass 100 with multiple functional effects. Optionally, the laminated glass 100 further includes multiple functional layers and a connecting layer 7 between the multiple functional layers. The connecting layer 7 is used to connect the multiple functional layers to form a functional layer group to provide the laminated glass 100 with corresponding functional effects.

[0069] In one possible embodiment, the thickness of the first functional layer 3 is greater than the thickness of the second functional layer 8. When external pressure acts on the laminated glass 100, the impact generated by the external pressure, when transmitted within the laminated glass 100, first reaches the first functional layer 3 and then reaches the second functional layer 8. The first functional layer 3 and the second functional layer 8 withstand different external impacts, with the first functional layer 3 bearing more impact and the second functional layer 8 bearing less impact. Therefore, in this application, by setting the first functional layer 3 as the thicker functional layer to withstand more impact, the first functional layer 3 and the second functional layer 8 are structurally stable, which is beneficial to the stability of the laminated glass 100.

[0070] In one possible embodiment, the ratio of the thickness of the first functional layer 3 to the thickness of the second functional layer 8 is 2:1 to 3:1. Specifically, the ratio of the thickness of the first functional layer 3 to the thickness of the second functional layer 8 can be, but is not limited to, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, or 3:1. When the ratio of the thickness of the first functional layer 3 to the thickness of the second functional layer 8 is 2:1 to 3:1, the impact energy of the first functional layer 3 and the second functional layer 8 against external pressure is more reasonably distributed, which is conducive to enhancing the mechanical strength of the laminated glass 100 and improving the stability of the laminated glass 100.

[0071] In one possible embodiment, the hardness of the first functional layer 3 is greater than the hardness of the second functional layer 8. When external pressure acts on the laminated glass 100, the impact generated by the external pressure, when transmitted within the laminated glass 100, first reaches the first functional layer 3 and then reaches the second functional layer 8. The first functional layer 3 and the second functional layer 8 bear different external impacts, with the first functional layer 3 bearing more impacts and the second functional layer 8 bearing less impacts. Therefore, in order to more reasonably distribute the external pressure impacts to be borne by the first functional layer 3 and the second functional layer 8, the present application sets the functional layer with greater hardness as the first functional layer 3 to withstand more impacts, thereby ensuring the structural stability of the first functional layer 3 and the second functional layer 8, which is beneficial to the stability of the laminated glass 100.

[0072] In one possible embodiment, the thickness of the connecting layer 7 is 0.1 mm to 0.4 mm. Specifically, the thickness of the connecting layer 7 may be 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, or 0.4 mm. In one possible embodiment, the thickness of the connecting layer 7 is 0.1 mm to 0.2 mm. Specifically, the thickness of the connecting layer 7 can be 0.1mm, 0.11mm, 0.12mm, 0.13mm, 0.14mm, 0.15mm, 0.16mm, 0.17mm, 0.18mm, 0.19mm, or 0.2mm; in order to ensure the structural stability of the first functional layer 3 and the second functional layer 8 so that they function normally, the adhesive layer is used to connect the first functional layer 3 and the second functional layer 8, and the lower the thickness of the adhesive layer, the greater its hardness can be ensured, so as to better improve the stability of the first functional layer 3 and the second functional layer 8; the thickness of the connecting layer 7 in this application is 0.1mm to 0.4mm, and further, the thickness of the connecting layer 7 is 0.1mm to 0.2mm; at this time, the thickness of the adhesive layer is lower and the hardness is higher, and the stability of the first functional layer 3 and the second functional layer 8 is higher.

[0073] In one possible embodiment, the second functional layer 8 is at least one of an infrared reflective layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film. The polymer dispersed liquid crystal film layer may be, but is not limited to, an SPD dimming film, an EC dimming film, or an LC dimming film. Specifically, the infrared reflective layer has a thickness ranging from 6 nm to 90 nm, and is used to reflect infrared rays from sunlight when the laminated glass 100 is used as a vehicle window glass to prevent the infrared rays from causing excessive temperature rise inside the vehicle. The ultraviolet absorption layer has a thickness ranging from 20 nm to 84 nm, and is used to absorb ultraviolet rays from sunlight when the laminated glass 100 is used as a vehicle window glass to prevent ultraviolet rays from damaging the interior of the vehicle. The touch film layer has a thickness ranging from 37 nm to 132 nm and is used to detect a touch signal applied to the laminated glass 100. When the laminated glass 100 is used as window glass on a vehicle, the touch film layer is used to detect the touch signal and control components of the vehicle such as window lights, induction lights, ambient lights, sensors, processors, etc. according to the signal. The polymer dispersed liquid crystal film layer has a thickness ranging from 25 nm to 98 nm and is used to adjust the transparent state or non-transparent state of the laminated glass 100 by changing to a transparent state or a non-transparent state.

[0074] In a possible implementation, the laminated glass 100 further includes a touch film layer, which is disposed between the second glass substrate 5 and the second adhesive layer 4 . The touch film layer is used to detect touch signals.

[0075] Optionally, the touch film layer is disposed on the second glass substrate 5, and a second adhesive layer 4 is disposed on the side of the touch film layer facing away from the second glass substrate 5. The touch film layer comprises a conductor and a controller, and narrow electrodes are plated on all four sides of the conductor of the touch film layer to form a low-voltage AC electric field within the conductor. When a user of the laminated glass 100 touches the second glass substrate 5, the human body also generates an electric field, forming a coupling capacitor between the finger and the conductor layer. Current emitted by the electrodes on the four sides flows to the contact point, and the current strength is proportional to the distance from the finger to the electrode. The controller located behind the second glass substrate 5 calculates the current ratio and strength to accurately determine the location of the touch point. When the laminated glass 100 is used as window glass in a vehicle, the touch film layer controls components of the vehicle, such as window lights, induction lights, ambient lights, sensors, and processors, based on the locations of different touch points.

[0076] Please refer to Tables 1 to 3, which show the physical and chemical properties of the laminated glass described in this application;

[0077] Among them, Examples 1-5 and Comparative Examples 1-5 are laminated glasses formed by stacking and pressing the first glass substrate, the first bonding layer, the first functional layer, the second bonding layer, and the second glass substrate in sequence; the average stress of the laminated glasses in Examples 1-5 and Comparative Examples 1-5 is 23 MPa; Examples 6-10 and Comparative Examples 6-10 are laminated glasses formed by stacking and pressing the first glass substrate, the first bonding layer, the third glass substrate, the second bonding layer, and the second glass substrate in sequence; the average stress of the laminated glasses in Examples 6-10 and Comparative Examples 6-10 is 25 MPa; Examples 11-15 and Comparative Examples 11-15 are laminated glasses formed by stacking and pressing the first glass substrate, the first bonding layer, the first functional layer, the bonding layer, the second functional layer, the second bonding layer, and the second glass substrate in sequence; the average stress of the laminated glasses in Examples 11-15 and Comparative Examples 11-15 is 25 MPa.

[0078] In Examples 1-15 and Comparative Examples 1-15, the average stress is measured by taking two points on each side of the laminated glass, that is, taking eight points on the four sides of the laminated glass, respectively testing the stress using a stress meter, and taking the average stress value of the eight points to obtain the average stress of the laminated glass. When two points are taken on the side of the laminated glass, the side of the laminated glass is divided into three equal parts by the two points.

[0079] In Examples 1-15 and Comparative Examples 1-15, the method for measuring the maximum static pressure is formulated in accordance with the national standard GB / T5137.1; the laminated glass of Examples 1-15 and Comparative Examples 1-15 described in this application is suspended and fixed in the air, and a tensile testing machine is used to apply a force within 40 mm of the center of the laminated glass until the laminated glass shatters. The force value at which the laminated glass shatters is recorded to obtain the maximum static pressure of the laminated glass.

[0080] Table 1

[0081]

[0082] As shown in Table 1, in Example 1, the thickness from the first adhesive layer to the second adhesive layer gradually increases, and the thickness from the first glass substrate to the second glass substrate gradually decreases; whereas in Comparative Example 1, the thickness from the first adhesive layer to the second adhesive layer remains unchanged, and the thickness from the first glass substrate to the second glass substrate remains unchanged; and in Example 1 and Comparative Example 1, the sum of the first adhesive layer and the second adhesive layer is equal, and the total thickness of the first glass substrate and the second glass substrate of Example 1 is less than the total thickness of the first glass substrate and the second glass substrate of Comparative Example 1.

[0083] However, in the maximum static pressure test, the maximum static pressure of Example 1 is greater than that of Comparative Example 1. This is because, during the maximum static pressure test, the impact of the external pressure first acts on the first glass substrate, and after being received and absorbed by the first glass substrate, it is transmitted toward the second glass substrate. The first glass substrate absorbs most of the impact force, while the second glass substrate absorbs a smaller impact force. Therefore, even though the thickness of Comparative Example 1 is greater, the second glass substrate does not show a significant gain. When the laminated glass is subjected to the impact of the external pressure, the laminated glass will deform under the action of the external pressure. When the external pressure acts on the laminated glass, The external pressure directly acts on the first glass substrate. In this case, the thickness of the first adhesive layer is designed to be relatively thin, which is conducive to ensuring the stability of the connection between the first glass substrate and other components of the laminated glass. Subsequently, when the impact of the external pressure reaches the second adhesive layer, the impact of the external pressure has been gradually weakened. In this case, the thickness of the second adhesive layer is designed to be relatively thick and the hardness is relatively low, so that the deformation tendency of the laminated glass under the action of the external pressure can be absorbed, thereby achieving a buffering effect and improving the overall stability of the laminated glass. Therefore, compared with Comparative Example 1, Example 1 has a larger maximum static pressure value and better structural stability.

[0084] In the comparison formed by Example 2 and Comparative Example 2, and the comparison formed by Example 3 and Comparative Example 3, the first adhesive layer and the second adhesive layer of the laminated glass forming the comparison are the same, the thickness of the first glass substrate to the thickness of the second glass substrate gradually decreases in Example 2 and Example 3, and the thickness of the first glass substrate to the thickness of the second glass substrate gradually increases in Comparative Example 2 and Comparative Example 3, and the total thickness of the first glass substrate and the second glass substrate are the same in Example 2 and Comparative Example 2, and the total thickness of the first glass substrate and the second glass substrate are the same in Example 3 and Comparative Example 3; in the maximum static pressure test, the maximum static pressure of Example 2 is greater than the maximum static pressure of Comparative Example 2, and the maximum static pressure of Example 3 is greater than the maximum static pressure of Comparative Example 3, which indicates that When the first adhesive layer and the second adhesive layer are identical, the impact caused by external pressure is absorbed by the first glass substrate and then transmitted toward the second glass substrate. The first glass substrate absorbs the vast majority of the impact force, while the second glass substrate absorbs a smaller impact force. Even though the total thickness of the first and second glass substrates is the same in Example 2 and Comparative Example 2, and the total thickness of the first and second glass substrates is the same in Example 3 and Comparative Example 3, the second glass substrate does not show a significant gain in improving the overall strength of the laminated glass. Therefore, compared with Comparative Example 2, and compared with Comparative Example 3, Example 2 and Example 3 have greater maximum static pressure values ​​and better structural stability.

[0085] In the comparison formed by Example 4 and Comparative Example 4, and the comparison formed by Example 5 and Comparative Example 5, the first glass substrate and the second glass substrate of the laminated glass forming the comparison are the same, the thickness of the first adhesive layer to the second adhesive layer of Example 4 and Example 5 gradually increases, and the thickness of the first adhesive layer to the second adhesive layer of Comparative Example 4 and Comparative Example 5 gradually decreases; and the total thickness of the first glass substrate and the second glass substrate of Example 4 and Comparative Example 4 is the same, and the total thickness of the first glass substrate and the second glass substrate of Example 5 and Comparative Example 5 is the same; in the maximum static pressure test, the maximum static pressure of Example 4 is greater than the maximum static pressure of Comparative Example 4, and the maximum static pressure of Example 5 is greater than the maximum static pressure of Comparative Example 5, which indicates that when the first glass substrate and the second glass substrate are the same, when the laminated glass is subjected to the impact of external pressure, The laminated glass will deform under the action of external pressure. When the external pressure acts on the laminated glass, the external pressure directly acts on the first glass substrate. In this case, the thickness of the first adhesive layer is designed to be relatively thin, which is conducive to ensuring the stability of the connection between the first glass substrate and other components of the laminated glass. Subsequently, when the impact of the external pressure reaches the second adhesive layer, the impact of the external pressure has been gradually weakened. In this case, the thickness of the second adhesive layer is designed to be relatively thick and the hardness is relatively low, so as to absorb the tendency of the laminated glass to deform under the action of external pressure, achieve a buffering effect, and improve the overall stability of the laminated glass. Therefore, compared with Comparative Example 4, Example 4 and Example 5 have larger maximum static pressure values ​​and better structural stability than Comparative Example 4, and compared with Comparative Example 5, Example 4 and Example 5 have higher maximum static pressure values ​​and better structural stability.

[0086] Table 2

[0087]

[0088] As shown in Table 2, in Example 6, the thickness of the first adhesive layer gradually increases to the thickness of the second adhesive layer; the thickness of the first glass substrate gradually decreases to the thickness of the third glass substrate to the second glass substrate; whereas in Comparative Example 6, the thickness of the first adhesive layer to the thickness of the second adhesive layer remains unchanged; the thickness of the first glass substrate remains unchanged to the thickness of the third glass substrate to the second glass substrate; and in Example 6 and Comparative Example 6, the sum of the first adhesive layer and the second adhesive layer is equal in both examples, and the total thickness of the first, third, and second glass substrates of Example 6 is equal to the total thickness of the first, third, and second glass substrates of Comparative Example 1.

[0089] However, in the maximum static pressure test, the maximum static pressure of Example 6 is greater than that of Comparative Example 6. This is because, in the maximum static pressure test, the impact caused by the external pressure first acts on the first glass substrate, and after being received and absorbed by the first glass substrate, it is transmitted to the third glass substrate and the second glass substrate. The first glass substrate absorbs most of the impact force, while the third glass substrate and the second glass substrate absorb a smaller impact force. Therefore, even though the thickness of the second glass substrate of Comparative Example 6 is greater than that of the glass substrate of Example 1, the second glass substrate does not show a significant gain. When the laminated glass is subjected to the impact caused by the external pressure, the laminated glass will deform under the action of the external pressure. When external pressure acts on the laminated glass, the external pressure acts directly on the first glass substrate. In this case, the thickness of the first adhesive layer is designed to be relatively thin, which is conducive to ensuring the stability of the connection between the first glass substrate and other components of the laminated glass. Subsequently, when the impact of the external pressure reaches the second adhesive layer, the impact of the external pressure has been gradually weakened. In this case, the thickness of the second adhesive layer is designed to be relatively thick and the hardness is relatively low, so that the deformation tendency of the laminated glass under the action of external pressure can be absorbed, achieving a buffering effect and improving the overall stability of the laminated glass. Therefore, compared with Comparative Example 6, Example 6 has a larger maximum static pressure value and better structural stability.

[0090] In the comparison formed between Example 7 and Comparative Example 7, the comparison formed between Example 8 and Comparative Example 8, the comparison formed between Example 9 and Comparative Example 9, and the comparison formed between Example 10 and Comparative Example 10, the first adhesive layer and the second adhesive layer of the laminated glass forming the comparison are the same.

[0091] The thickness of the first glass substrate to the third glass substrate to the second glass substrate of Example 7, Example 8, Example 9, and Example 10 gradually decreases, while the thickness of the first glass substrate to the third glass substrate to the second glass substrate of Comparative Example 7, Comparative Example 8, Comparative Example 9, and Comparative Example 10 gradually increases, and the total thickness of the first glass substrate, the third glass substrate, and the second glass substrate of Example 7 and Comparative Example 7 is equal, the total thickness of the first glass substrate, the third glass substrate, and the second glass substrate of Example 8 and Comparative Example 8 is equal, the total thickness of the first glass substrate, the third glass substrate, and the second glass substrate of Example 9 and Comparative Example 9 is equal, and the total thickness of the first glass substrate, the third glass substrate, and the second glass substrate of Example 10 and Comparative Example 10 is equal.

[0092] In the maximum static pressure test, the maximum static pressure of Example 7 was greater than that of Comparative Example 7, the maximum static pressure of Example 8 was greater than that of Comparative Example 8, the maximum static pressure of Example 9 was greater than that of Comparative Example 9, and the maximum static pressure of Example 10 was greater than that of Comparative Example 10. This indicates that when the first adhesive layer and the second adhesive layer are the same, the impact caused by the external pressure is absorbed by the first glass substrate and then transmitted to the third glass substrate and the second glass substrate. The first glass substrate absorbs most of the impact force, while the third glass substrate and the second glass substrate absorb less impact force. Even though the second glass substrate of Example 7 is thinner than that of Comparative Example 7 and the second glass substrate of Example 8 is thinner than that of Comparative Example 8, the second glass substrate does not show a significant gain in improving the overall strength of the laminated glass. Therefore, compared with Comparative Example 7, and compared with Comparative Example 8, Example 7 and Example 8 have higher maximum static pressure values ​​and better structural stability.

[0093] In summary, when multiple glass substrates and multiple adhesive layers are alternately stacked to prepare laminated glass, the multiple glass substrates are arranged in a manner of gradually decreasing thickness in one direction, and the multiple adhesive layers are arranged in a manner of gradually increasing thickness in the same direction; under the premise that the total thickness of the laminated glass is determined, laminated glass with higher structural stability can be obtained; in other words, under the premise that the structural stability requirements are determined, laminated glass with less material and lighter weight can be obtained.

[0094] Table 3

[0095]

[0096] As shown in Table 3, in Example 11, the thickness from the first adhesive layer to the second adhesive layer gradually increases, and the thickness from the first glass substrate to the second glass substrate gradually decreases. In Comparative Example 11, the thickness from the first adhesive layer to the second adhesive layer remains unchanged, and the thickness from the first glass substrate to the second glass substrate remains unchanged. In addition, the sum of the first adhesive layer and the second adhesive layer in Example 11 and Comparative Example 11 is equal, and the total thickness of the first glass substrate and the second glass substrate in Example 1 is less than the total thickness of the first glass substrate and the second glass substrate in Comparative Example 1.

[0097] However, in the maximum static pressure test, the maximum static pressure of Example 11 is greater than that of Comparative Example 11. This is because, during the maximum static pressure test, the impact of the external pressure first acts on the first glass substrate, and after being received and absorbed by the first glass substrate, it is transmitted toward the second glass substrate. The first glass substrate absorbs most of the impact force, while the second glass substrate absorbs a smaller impact force. Therefore, even though the thickness of Comparative Example 11 is greater, the second glass substrate does not show a significant gain. When the laminated glass is subjected to the impact of the external pressure, the laminated glass will deform under the action of the external pressure. When the external pressure acts on the laminated glass, the laminated glass will deform under the action of the external pressure. In the case of laminated glass, the external pressure directly acts on the first glass substrate. In this case, the thickness of the first adhesive layer is designed to be relatively thin, which is beneficial for ensuring the stability of the connection between the first glass substrate and other components of the laminated glass. Subsequently, when the impact of the external pressure reaches the second adhesive layer, the impact of the external pressure has been gradually weakened. In this case, the thickness of the second adhesive layer is designed to be relatively thick and the hardness is relatively low, so that the deformation tendency of the laminated glass under the action of the external pressure is absorbed, achieving a buffering effect and improving the overall stability of the laminated glass. Therefore, compared with Comparative Example 11, Example 11 has a larger maximum static pressure value and better structural stability.

[0098] In the comparison between Example 12 and Comparative Example 12, and between Example 13 and Comparative Example 13, the first adhesive layer and the second adhesive layer of the laminated glass forming the comparison are the same; the thickness of the first glass substrate gradually decreases towards the thickness of the second glass substrate in Example 12 and Example 13, while the thickness of the first glass substrate gradually increases towards the thickness of the second glass substrate in Comparative Example 12 and Comparative Example 13; the total thickness of the first glass substrate and the second glass substrate are the same in Example 12 and Comparative Example 12, while the total thickness of the first glass substrate and the second glass substrate are the same in Example 13 and Comparative Example 13; in the maximum static pressure test, the maximum static pressure of Example 12 is greater than that of Comparative Example 12, while the maximum static pressure of Example 13 is greater than that of Comparative Example 13, which indicates that This indicates that when the first adhesive layer and the second adhesive layer are identical, the impact of external pressure is absorbed by the first glass substrate and then transmitted toward the second glass substrate. The first glass substrate absorbs the vast majority of the impact force, while the second glass substrate absorbs a smaller amount of the impact force. Even though the total thickness of the first and second glass substrates in Example 12 and Comparative Example 12 is the same, and the total thickness of the first and second glass substrates in Example 13 and Comparative Example 13 is the same, the second glass substrate does not show a significant gain in improving the overall strength of the laminated glass. Therefore, compared with Comparative Example 12, and compared with Comparative Example 13, Example 12 and Example 13 have larger maximum static pressure values ​​and better structural stability.

[0099] In the comparison formed by Example 14 and Comparative Example 14, and the comparison formed by Example 15 and Comparative Example 15, the first glass substrate and the second glass substrate of the laminated glass forming the comparison are the same, the thickness of the first adhesive layer to the second adhesive layer of Example 14 and Example 15 gradually increases, and the thickness of the first adhesive layer to the second adhesive layer of Comparative Example 14 and Comparative Example 15 gradually decreases; and the total thickness of the first glass substrate and the second glass substrate of Example 14 and Comparative Example 14 is the same, and the total thickness of the first glass substrate and the second glass substrate of Example 15 and Comparative Example 15 is the same; in the maximum static pressure test, the maximum static pressure of Example 14 is greater than the maximum static pressure of Comparative Example 14, and the maximum static pressure of Example 15 is greater than the maximum static pressure of Comparative Example 15, which indicates that when the first glass substrate and the second glass substrate are the same, when the laminated glass is subjected to external pressure to form After the impact of the external pressure, the laminated glass will deform under the action of the external pressure. When the external pressure acts on the laminated glass, the external pressure directly acts on the first glass substrate. At this time, the thickness of the first adhesive layer is designed to be thinner, which is conducive to ensuring the stability of the connection between the first glass substrate and other components of the laminated glass. Subsequently, when the impact caused by the external pressure reaches the second adhesive layer, the impact caused by the external pressure has been gradually weakened. At this time, the thickness of the second adhesive layer is designed to be thicker and the hardness is smaller, so as to absorb the tendency of the laminated glass to deform under the action of the external pressure, achieve a buffering effect, and improve the overall stability of the laminated glass. Therefore, compared with Comparative Example 14, Example 14 and Example 15 have larger maximum static pressure values ​​and better structural stability than Comparative Example 15.

[0100] Referring to FIG. 4 , the present application further provides a vehicle 200 , including:

[0101] Vehicle body 9;

[0102] In the laminated glass 100 described in the present application, the first glass substrate 1 faces the outside of the vehicle body, and the second glass substrate 5 faces the inside of the vehicle body 9 .

[0103] The laminated glass 100 described in the present application increases the thickness of the stress-bearing side of the laminated glass 100 and reduces the thickness of the non-stress-bearing side of the laminated glass 100, so as to improve the overall mechanical strength of the laminated glass 100 and reduce the weight of the laminated glass 100; the vehicle windows of the vehicle 200 described in the present application are equipped with the laminated glass 100 described in the present application, and the vehicle windows have high strength and good safety performance parameters. At the same time, by reducing the weight of the windows, the total weight of the vehicle 200 is reduced, the energy consumption of the vehicle 200 is reduced, and the vehicle 200 has a better sound insulation effect.

[0104] Mentioning "embodiments" and "implementation methods" in this application means that the specific features, structures or characteristics described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, unless there is a contradiction between them.

[0105] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application has been described in detail with reference to the above preferred implementation modes, ordinary technicians in this field should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A laminated glass, characterized in that: The invention comprises a first glass substrate, a first adhesive layer, a first functional layer, a second adhesive layer and a second glass substrate, wherein the first glass substrate, the first adhesive layer, the first functional layer, the second adhesive layer and the second glass substrate are stacked in sequence; the thickness of the first glass substrate is greater than that of the second glass substrate, and the thickness of the first adhesive layer is less than that of the second adhesive layer.

2. The laminated glass according to claim 1, wherein: A ratio of a thickness of the first glass substrate to a thickness of the second glass substrate is 1.17:1 to 2.91:

1.

3. The laminated glass according to claim 2, wherein: A ratio of a thickness of the first glass substrate to a thickness of the second glass substrate is 1.17:1 to 1.5:

1.

4. The laminated glass according to claim 1, wherein: A ratio of a thickness of the first adhesive layer to a thickness of the second adhesive layer is 1:8 to 1:1.

1.

5. The laminated glass according to claim 1, wherein: The mechanical strength of the first glass substrate is greater than that of the second glass substrate.

6. The laminated glass according to claim 1, wherein: The hardness of the second bonding layer is smaller than that of the first bonding layer.

7. The laminated glass according to claim 1, wherein: The first functional layer is at least one of an infrared reflection layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film.

8. The laminated glass according to any one of claims 1 to 6, wherein: The first functional layer is a third glass substrate. The thickness of the first glass substrate is greater than that of the third glass substrate. The thickness of the third glass substrate is greater than that of the second glass substrate.

9. The laminated glass according to claim 8, wherein: A ratio of the thickness of the first glass substrate, the thickness of the third glass substrate, and the thickness of the second glass substrate is (2.91 to 2):(2 to 1.17):

1.

10. The laminated glass according to claim 9, wherein: A ratio of the thickness of the first glass substrate, the thickness of the third glass substrate, and the thickness of the second glass substrate is (1.5 to 1.3):(1.3 to 1.17):

1.

11. The laminated glass according to claim 8, wherein: The mechanical strength of the first glass substrate is greater than that of the third glass substrate, and the mechanical strength of the third glass substrate is greater than that of the second glass substrate.

12. The laminated glass according to any one of claims 1 to 7, wherein: The laminated glass further includes a second functional layer and a connecting layer. The second functional layer is arranged between the first functional layer and the second adhesive layer. The connecting layer is arranged between the first functional layer and the second functional layer for connecting the first functional layer and the second functional layer.

13. The laminated glass according to claim 12, wherein: The thickness of the first functional layer is greater than that of the second functional layer.

14. The laminated glass according to claim 12, wherein: The ratio of the thickness of the first functional layer to the thickness of the second functional layer is 2:1 to 3:

1.

15. The laminated glass according to claim 12, wherein: The hardness of the first functional layer is greater than that of the second functional layer.

16. The laminated glass according to claim 12, wherein: The thickness of the connecting layer is 0.1 mm to 0.4 mm.

17. The laminated glass according to claim 16, wherein: The thickness of the connecting layer is 0.1 mm to 0.2 mm.

18. The laminated glass according to claim 12, wherein: The second functional layer is at least one of an infrared reflection layer, an ultraviolet absorption layer, a touch film layer, a polymer dispersed liquid crystal film layer, and a display film.

19. The laminated glass according to claim 12, wherein: The laminated glass further includes a touch film layer, which is disposed between the second glass substrate and the second adhesive layer. The touch film layer is used to detect touch signals.

20. A vehicle, characterized in that: include: Vehicle body; as well as The laminated glass according to any one of claims 1 to 19, wherein the first glass substrate faces the outside of the vehicle body, and the second glass substrate faces the inside of the vehicle body.

Citation Information

Patent Citations

  • Laminated glass for vehicles

    CN108290787A

  • Hollow laminated glass and manufacturing method thereof

    CN112901030A

  • Laminated glass for vehicle window

    JP2008290900A

  • Glass sheet-resin plate laminate

    JP2014136338A

  • High rigity interlayers and light weight laminated multiple layer panels

    US20130236711A1